Retrospective study of livestock vaccine coverage and trend in Lemu and Bilbilo Woreda, Arsi Zone, Ethiopia - Debele Hordofa Feyisa; Meseret kedir; Leta Shene (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Vaccination is one of the most efficient tools for protection against clinical disease of livestock and reduces the rate of spread of infection. The study was conducted using secondary data that recorded at Lemu and Bilbilo Woreda veterinary clinic with the objective to assess the vaccination coverage in the study area from March to September 2021. Results revealed the most commonly practiced vaccine were bacterial and viral diseases from secondary data recorded were Lumpy skin disease, Black leg, Pasteurellosis, New castle, Gumboro disease, chicken pox, Fowl pox, and Fowl Cholera. The percentage of vaccine coverage for lumpy skin disease decreases from a year 2017 (51.1%) to 2021(24%). The majority of Goat (96.7%) was vaccinated against goat pox during 2017 and the 0% Anthrax vaccine for Goat in 2021. Only 7.3% sheep in 2017 and near 37.4% in 2021 were vaccinated with sheep pox from total population. About 87.4% of equines were vaccinated from total population in 2017. The proportion of Newcastle disease and Gumboro disease vaccine coverage were 35% and 15.4%, respectively. Dog vaccination against rabies is increases from a year 2017 (4.8%) to 2020 (11%) in except 0.5% in 2021. The vaccine trends were fluctuating and/or decreasing from year to year. However, vaccine trend for Anthrax of cattle was increasing from year to year. It is therefore, suggested that implementation of planed and regularly vaccination of animal was very important for diseases control and prevention are recommended in order to decrease disease reoccurrence in the area.